Students’ perception and expectation toward learning German receptive skills - Karuna, Kalvin; Serpara, Henderika; Nikijuluw, Maria Martha (Intelektual Pustaka Media Utama, 2025)
The purpose of this study is to describe the perceptions and expectations of German language students, especially in terms of receptive skills. This study asks two main questions: i) what are the expectations of students towards learning German and ii) how are students' perceptions of German learning, especially reading and listening, the data sources for this research are students of the German Language Education Study Program. The research instruments were questionnaires and in-depth interviews. The data were analyzed descriptively, which showed that i) In general (98%) students have high expectations to study and work in Germany, for example, following the